Split application of inorganic fertilizers in potato (Solanum tuberosum L.)-hybrid maize (Zea mays L.) Intercropping system (Bangladesh Journal of Agricultural Research, 2013)
The experiment was conducted at the research field of Agronomy Division, BARI, Joydebpur, Gazipur during the rabi season of 2009-10 and 2010-11 to find out economic fertilizer dose along with time of split application of fertilizers to potato-hybrid maize intercropping system for higher productivity. Six treatment combinations were derived through combining two fertilizer doses F1= 255-55-140-40-6-2 and F2=320-73-170-50-6-2 kg/ha NPKSZnB and three levels of split applications viz., S1= 1/3 N and full of PKSZnB (basal as broadcast) + 1/3 N top dressed at 30 DAP (days after planting) of potato + 1/3 N top dressed after potato harvest, S2= 1/3 N & ½ of PKSZnB (basal in potato rows) + ½ of PKSZnB (basal for maize) + 1/3 N top dressed at 30 DAP of potato + 1/3 N top dressed after potato harvest and S3= ¼ N & ½ of PKSZnB (basal in potato rows) + ½ of PKSZnB (basal for maize) + ¼ N top dressed at 30 DAP of potato + ¼ N top dressed at 60 DAP of potato to maize rows only + ¼ N top dressed after potato harvest. Sole crops of hybrid maize and potato with recommended fertilizer dose of 255-55-140-40-6-2 and 135-30-135-15-4-0.5 kg/ha NPKSZnB were included for comparison. The highest tuber yield of potato (24.24 t/ha) and grain yield of maize (9.48 t/ha) were obtained from respective sole crops with recommended fertilizer management. The highest potato equivalent yield (30.26 t/ha), gross return (Tk. 363120/ha), gross margin (Tk. 258620/ha), and benefit cost ratio (3.47) were obtained from F1S3. The results revealed that fertilizer dose of 255-55-140-40-6-2 kg/ha NPKSZnB along with its split application, ¼ N and ½ of PKSZnB (basal in potato rows) + ½ of PKSZnB (basal for maize) + ¼ N top dressed at 30 DAP of potato + ¼ N top dressed at 60 DAP of potato to maize rows only + ¼ N top dressed after potato harvest, might be economically profitable for potato hybrid maize intercropping system. DOI: http://dx.doi.org/10.3329/bjar.v38i3.16971 Bangladesh J. Agril. Res. 38(3): 447-453, September 2013